Factors Influencing Users in Using Mobile Banking with the Extended Unified Technology Acceptance and Use of Technology Model - Supandik, Ujang Joko; Pranama, Edwin; Setyati, Endang (PT. Anagata Sembagi Education, 2025)
As one of the most innovative and new technologies, Mobile banking is a good example of the breakthrough of mobile technology in the banking sector, allowing customers to independently perform financial transactions (i.e. balance inquiries, fund transfers, bill payments) via mobile devices, smartphones, or Personal Digital Assistants (PDAs) at a time and place chosen by the customer. Customers in Indonesia have now widely used the internet for financial services. This study aims to analyze the factors that influence users in using mobile banking in Indonesia using the Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model. This study identifies key variables such as security, trust, performance expectations, social influence and user intentions in adopting mobile banking in Indonesia. The method used in this research is to conduct a survey by distributing questionnaires using Google Form and distributed via WhatsApp, Instagram and word of mouth, at least 400 respondents to mobile banking users. The results of the analysis show that all factors have a significant influence on user intention to use mobile banking. In addition, the Trust and security variables play a very important role in adopting mobile banking. These findings are expected to provide solutions for mobile banking providers in.